2015
DOI: 10.1103/physrevlett.115.054101
|View full text |Cite
|
Sign up to set email alerts
|

Transient Uncoupling Induces Synchronization

Abstract: Finding conditions that support synchronization is a fertile and active area of research with applications across multiple disciplines. Here we present and analyze a scheme for synchronizing chaotic dynamical systems by transiently uncoupling them. Specifically, systems coupled only in a fraction of their state space may synchronize even if fully coupled they do not. Although, for many standard systems, coupling strengths need to be bounded to ensure synchrony, transient uncoupling removes this bound and thus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 36 publications
1
64
0
Order By: Relevance
“…A central problem in physics is understanding the synchronization of stochastic oscillators12345, but this problem is largely unstudied in biology6, particularly in the context of circadian rhythms. Most measurements on the biological clock are made on millions of cells to understand the mechanism of telling time7.…”
mentioning
confidence: 99%
“…A central problem in physics is understanding the synchronization of stochastic oscillators12345, but this problem is largely unstudied in biology6, particularly in the context of circadian rhythms. Most measurements on the biological clock are made on millions of cells to understand the mechanism of telling time7.…”
mentioning
confidence: 99%
“…With χ(t), the two AR oscillators are intermittently and periodically coupled unlike the coupling scheme of Schröder et al Nevertheless, as will be shown in the next section, the intermittently coupled nonidentical AR oscillators exhibit partial synchronization via the mechanism underlying the coupled identical Rössler oscillators studied in [20].…”
Section: Augmented Rössler Equations and Their Synchronizabilitymentioning
confidence: 96%
“…Recently, Schröder et al reported that transient uncoupling of nonlinear oscillators does not interrupt chaotic synchronization [20]. They observed the dynamical stability of the synchronization manifold for unidirectionally diffusively coupled Rössler oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…We first highlight that a wide range of systems with sparse connectivity are non-synchronizable, even if they exhibit at least indirect connections (paths) between any two units. We then systematically extend a method of transient uncoupling that has been studied for two coupled oscillators25 to propose a general scheme of interaction control applicable to any network. We show that localizing the interactions among the units to small regions of state space not only extends the synchronization range but newly creates synchrony, even for non-synchronizable networks.…”
mentioning
confidence: 99%